Fluid retention in patients with paroxysmal and permanent atrial fibrillation and heart failure - V. V. Kirillova; L. A. Sokolova; A. A. Garganeyeva; V. N. Meshchaninov; R. E. Batalov (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study the fluid retention in patients with atrial fibrillation (AF) and heart failure (CHF) in order to adjust the therapy.Material and methods. In patients with class I-III HF and paroxysmal (n=16) and permanent AF (n=15), compared with the control group (n=14), the content of total body water (TBW) and extracellular fluid (ECF) was studied by bioelectrical impedance vector analysis. Using echocardiography, the maximum and minimum diameters of the coronary sinus were determined. TBW was assessed by the active resistance at a frequency of 50 kHz, while extracellular fluid — at a frequency of 5 kHz.Results. The content of BW and ECF in patients with AF and HF is higher than in the control group, with a higher content in patients with permanent AF compared to the paroxysmal (p<0,05): resistance at a frequency of 50 kHz in patients with permanent AF, paroxysmal AF, and in the control group was 505,00+27,69, 610,44+42,46, and 669,71+20,51 ohms, respectively; active resistance at a frequency of 5 kHz — 564,29+30,28; 670,81+39,74, and 764,43+21,75 ohms, respectively. The maximum and minimum diameters of the coronary sinus in patients with AF and HF were larger than in the control group, with a larger minimum diameter in permanent AF compared with the paroxysmal (p<0,05): the maximum diameter of the coronary sinus in patients with paroxysmal AF, permanent AF and in the control group was 22,17±0,57, 23,49±0,96, and 14,97±0,33 mm, respectively, and the minimum diameter of the coronary sinus was 12,63±0,62, 15,29±1,02, and 5,12±0,35 mm, respectively.Conclusion. Patients with AF and HF have an increased content of TBW and ECF and a dilated coronary sinus. In patients with permanent AF in comparison with paroxysmal AF, the content of TBW and ECF is higher.